2014
DOI: 10.1089/thy.2013.0214
|View full text |Cite
|
Sign up to set email alerts
|

Radiation-Associated Small Cell Neuroendocrine Carcinoma of the Thyroid: A Case Report with Molecular Analyses

Abstract: Background: Neuroendocrine tumor (NET) of the thyroid other than medullary carcinoma is extremely rare. We describe here a case of calcitonin-negative small cell neuroendocrine carcinoma (SCNEC), which occurred in a thyroid gland that had previously been irradiated at high dose (60Gy) for pharyngeal cancer, with molecular analyses for follicular cell origin. Patient Findings: The tumor cells were small with fine chromatin, inconspicuous nucleoli, and inapparent cytoplasm, and showed neuroendocrine architecture… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 26 publications
0
14
0
Order By: Relevance
“…PTEN plays an essential role as a negative regulator in the PI3K-AKT-mTOR pathway, which has been found to be somatically deleted, mutated, and/or silenced in various sporadically occurring cancers such as glioblastoma, malignant melanoma, and thyroid, breast, endometrial, and ovarian carcinomas [31][32][33][34][35][36][37]. Functional PTEN inactivation might occur through deletion, LOH, or other mutations [6,38]. In sporadic pancreatic NEN, somatic PTEN mutations including indels and missense mutations have been found in 7.3 % of cases by whole exomic sequencing [39].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PTEN plays an essential role as a negative regulator in the PI3K-AKT-mTOR pathway, which has been found to be somatically deleted, mutated, and/or silenced in various sporadically occurring cancers such as glioblastoma, malignant melanoma, and thyroid, breast, endometrial, and ovarian carcinomas [31][32][33][34][35][36][37]. Functional PTEN inactivation might occur through deletion, LOH, or other mutations [6,38]. In sporadic pancreatic NEN, somatic PTEN mutations including indels and missense mutations have been found in 7.3 % of cases by whole exomic sequencing [39].…”
Section: Discussionmentioning
confidence: 99%
“…Loss of heterozygosity (LOH) of the tumor suppressor phosphatase and tensin homolog (PTEN) concurrent to intrachromosomal 10 deletion is a common genetic event in small cell neuroendocrine carcinomas (NECs) of the lung and gastrointestinal tract [4,5], and we previously described a highgrade neuroendocrine tumor (NET) of the thyroid carrying PTEN alterations [6]. For such tumors, the tyrosine kinase inhibitor sunitinib and the mTOR inhibitor everolimus have shown antitumor effects and improved prognosis [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Despite limited sampling, the findings herein fit well with those of a high-grade neuroendocrine carcinoma. Such tumors are very rare in the thyroid gland and most have been small cell carcinomas ( 1 , 2 , 3 , 4 , 5 ). Grading of neuroendocrine tumors is organ specific, and the grading of thyroid neuroendocrine carcinomas has not yet been described, but by both the mitotic rate and Ki67 positive rate, this tumor would be a high-grade neuroendocrine carcinoma in any organ.…”
Section: Discussionmentioning
confidence: 99%
“…Mussazhanova et al 21 reported the case of a calcitoninnegative NET where the tumor cells invaded several vessels and had metastasized to regional lymph nodes, which occurred in the thyroid of a patient previously having been irradiated at a high dose (60 Gy) for pharyngeal cancer. Immunohistochemically, the tumor cells were strongly positive for neuroendocrine markers and Tg, a marker of thyroid follicular cells, but negative for calcitonin and CEA.…”
Section: Discussionmentioning
confidence: 99%